2008
DOI: 10.1007/s10519-008-9250-z
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in Drinking Behavior of Twin’s Friends: Moderation of Heritability of Alcohol Use

Abstract: Previous research has indicated that friends' drinking may influence alcohol use in adolescents and young adults. We explored whether similarities in the drinking behavior of friends of twins influence the genetic architecture of alcohol use in adolescence and young adulthood. Survey data from The Netherlands Twin Register were available for 1,526 twin pairs aged 16-25 years. We categorized the twin pairs as concordant (both report similar alcohol use in their friends) or discordant for the alcohol use of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Other studies have found no gender differences (Alati et al, 2014;McGue, Malone, Keyes, & Iacono, 2014;Poelen, Scholte, Willemsen, Boomsma, & Engels, 2007), and at least one study demonstrated stronger effects of parental drinking for boys (Cleveland & Wiebe, 2003).…”
Section: The Relationship Between Parent Heavy Episodic Drinking and mentioning
confidence: 91%
See 1 more Smart Citation
“…Other studies have found no gender differences (Alati et al, 2014;McGue, Malone, Keyes, & Iacono, 2014;Poelen, Scholte, Willemsen, Boomsma, & Engels, 2007), and at least one study demonstrated stronger effects of parental drinking for boys (Cleveland & Wiebe, 2003).…”
Section: The Relationship Between Parent Heavy Episodic Drinking and mentioning
confidence: 91%
“…Many longitudinal studies lack information about father's drinking, or average reports across parents for analysis (Donovan & Molina, 2014;Duncan, Gau, Duncan, & Strycker, 2011;Latendresse et al, 2008). Amongst studies that do examine the role of both mother's and father's drinking, some show that only mother's drinking is significantly associated with adolescent drinking after controlling for father's drinking (Chassin, Pillow, Curran, Molina, & Barrera Jr, 1993;Macleod et al, 2008;Poelen et al, 2007). Others report statistically significant coefficients for both parents (Alati et al, 2014;Chassin, Curran, Hussong, & Colder, 1996;Haugland et al, 2015;Kelly et al, 2016;McGue et al, 2014;van der Zwaluw et al, 2008), but do not explicitly test whether the mother's or the father's drinking has stronger associations with adolescent drinking.…”
Section: The Relationship Between Parent Heavy Episodic Drinking and mentioning
confidence: 99%
“…Twin and family studies have consistently suggested that alcohol-related phenotypes are genetically influenced, with heritability estimates for alcohol abuse and dependence estimated at ~50–60% [24]; estimates for other alcohol-related phenotypes are sometimes lower [57]. The heritability of alcohol use typically increases beyond adolescence [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Research has also examined more refi ned Gene × Environment interactions. For example, one study indicated that genetic factors were more predictive of alcohol use in twin pairs than the twins ' association with peers who drank alcohol (see Poelen, Engels, Scholte, Boomsma, & Willemsen, 2009 ). Another, more recent study ( Larsen et al, 2010 ) examined college students in the Netherlands and found a relationship between the DRD4 7-repeat polymorphism and sensitivity to other students ' drinking behaviors.…”
Section: Examination Of Genetic Overlap In Addictive Behaviors Among ...mentioning
confidence: 99%